2006
DOI: 10.1086/498897
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Respiratory Viruses, Temperature, and Other Climatic Parameters with the Incidence of Invasive Pneumococcal Disease in Sydney, Australia

Abstract: This study suggests that RSV infection and influenza contribute to IPD incidence peaks differently for children than for adults. Data from other geographic areas and more rigorous study designs are required to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
72
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(84 citation statements)
references
References 20 publications
8
72
0
4
Order By: Relevance
“…Increased relative humidity was associated with increased IPD incidence in New Zealand, but not in Australia 12, 13 . Low sunlight and temperature are consistently associated with high pneumonia incidence in time series studies in temperate settings, where annual peaks of lower respiratory infections occur during the short days of winter 10,[12][13][14][15][16] . The association between temperature and respiratory infections in children is inconsistent in time series studies from tropical settings, suggesting temperature is unlikely to be an important driver of pneumonia incidence in the tropics [6][7][8][9][10][11] .…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Increased relative humidity was associated with increased IPD incidence in New Zealand, but not in Australia 12, 13 . Low sunlight and temperature are consistently associated with high pneumonia incidence in time series studies in temperate settings, where annual peaks of lower respiratory infections occur during the short days of winter 10,[12][13][14][15][16] . The association between temperature and respiratory infections in children is inconsistent in time series studies from tropical settings, suggesting temperature is unlikely to be an important driver of pneumonia incidence in the tropics [6][7][8][9][10][11] .…”
Section: Discussionmentioning
confidence: 85%
“…Rainfall is not convincingly associated with pneumonia incidence in time series studies from temperate settings 10,12,13 . Relative humidity is not consistently associated with RSV incidence in temperate settings, however dew point temperature is more consistently (negatively) associated 10 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…RSV and IPD are associated in infants/children,5, 17, 26, 29, 30 and influenza and IPD in the elderly 26, 28, 30. The strongest associations between respiratory viruses and pneumococcal disease occur among the older age groups 18, 20, 22, 26.…”
Section: Discussionmentioning
confidence: 99%
“…The strength of the interaction between influenza or influenza‐like illness (ILI) and IPD at population level, however, varies across studies from non‐existent to significant 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27. Studies looking at specific respiratory viruses also showed inconsistent results 5, 28, 29, 30. In addition, most studies did not control for seasonality of the pathogens or used a sine/cosine function to adjust for it 27.…”
Section: Introductionmentioning
confidence: 99%